Patient-Reported Burden of Severe Alopecia Areata: First Results from the Multinational Alopecia Areata Unmet Need Survey - Bewley,Anthony; Figueras-Nart,Ignasi; Zhang,Jainzhong; Guerreiro,Mariana; Tietz,Nicole; Chtourou,Sami; Durand,Frederick; Blume-Peytavi,Ulrike (Clinical, Cosmetic and Investigational Dermatology, 2024)
Anthony Bewley,1 Ignasi Figueras-Nart,2 Jainzhong Zhang,3 Mariana Guerreiro,4 Nicole Tietz,4 Sami Chtourou,4 Frederick Durand,4 Ulrike Blume-Peytavi5 1Department of Dermatology, The Royal London Hospital & Queen Mary University, London, UK; 2Department of Dermatology, University Hospital de Bellvitge, Barcelona, Spain; 3Department of Dermatology, Peking University People’s Hospital, Beijing, People’s Republic of China; 4Eli Lilly and Company Ltd, Indianapolis, IN, USA; 5Charité – Universitätsmedizin Berlin, corporate member of Freie Universität Berlin and Humboldt-Universität zu Berlin, Department of Dermatology, Venereology and Allergology, Berlin, GermanyCorrespondence: Anthony Bewley, Department of Dermatology, The Royal London Hospital & Queen Mary University, London, UK, Tel +44 020 7767 3200, Email anthony.bewley@nhs.netPurpose: Alopecia areata (AA) is an autoimmune disease characterized by hair loss that has significant psychosocial implications. This study aims to describe the patient-reported burden of severe AA, coping mechanism and information needs using data from the multinational AA Patient Satisfaction and Unmet Need Survey.Patients and Methods: Participants with current or previous ≥ 50% scalp hair loss (n = 747) were recruited from 11 countries and completed a web-based survey that assessed demographics, clinical characteristics, disease burden and psychosocial impact. Data were stratified according to sex, current age, disease duration and current severity of scalp hair loss.Results: The mean (SD) age of participants was 43.8 (7.1) years, 55.3% were women, and 63.5% reported AA symptoms within 6 months of diagnosis. Most participants had black or brown hair (88.4%), reported a disease duration of 2 years or more (75.6%) and had current scalp hair loss of ≥ 50% (87.4%). Severe hair loss also extended to eyebrow (46.9%), eyelash (48.7), beard (61.5%) and body hair (73.2%). Participants commonly reported comorbidities such as anxiety (26.1%), depression (18.1%) and ...